STRATEGY ANALYSIS OF ABILITY AND WILLINGNESS TO PAY ABOUT COMMUNITY BASED COMMUNAL WWTP MANAGEMENT IN BANDUNG - Ayu Sarastiana, Nitya
: In 2020, the coverage of sanitation services in Bandung is only around 81.25%, so to increase the coverage of sanitation services, there is a community-based WWTP (Wastewater Treatment Plant) program. However, along the way, there are problems in management and financing. This research was conducted to analyze how the management of communal WWTP can be adaptable, effective and effective, to determine the willingness and ability of the community to manage the Communal IPAL as well as to analyze strategies and recommendations for its sustainability in Bandung City. The study was conducted in six kelurahan in Bandung City based on the level of sanitation risk and the proportion of low-income people. The research was conducted by observation, interviews with the KPP and distributing questionnaires to the local community with 20 respondents per location. The data analysis method is divided into two, namely the communal WWTP management data analysis and the WTP data analysis method with the stated preference method, the contingent valuation method and ATP with the household budget method. Meanwhile, the result of this research is WWTP in Bandung City already can adapt, efficient and effective. Also for the willingness and ability to pay, each research location provided various WTP and ATP values. The average value of WTP in the range of Rp. 3,100 - Rp 6,825, while the average value of ATP was Rp. 5,370 - Rp. 10,304. Then the analysis of the factors that influence it with sperman-rho test, based on the results of the test, the level of expenditure and satisfaction have a significant relationship with willingness to pay. After analyzing the WTP and ATP calculations as well as the management of the Communal WWTP, a strategy and recommendations were made to improve the management of the Communal WWTP with SWOT method, financing recommendations and the quadruple helix model.